Strategi Guru dalam Mengatasi Kendala Waktu pada Pembelajaran Fiqih Berbasis Contextual Teaching and Learning: Studi Kualitatif - Ananta, Ripka; Istiqomah, Najwatul; Faradiba Balbisi, Nafilah; Asna Maqashida Kholiza; Anita Khusna Manzila; Dimas Setiaji Prabowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teachers’ strategies in overcoming time constraints in fiqh learning based on Contextual Teaching and Learning (CTL) at Madrasah Ibtidaiyah. CTL is implemented because it has been proven effective in helping students understand learning materials through real-life experiences. However, in practice, teachers face challenges, particularly limited instructional time, especially during group discussions that require considerable time to reach agreements and find solutions. This research employs a qualitative approach with a field research design. Data collection techniques include interviews and documentation. The findings reveal that the implementation of CTL encourages students to construct their understanding independently through real-life examples. However, field facts indicate that discussion activities often take longer than planned due to varying levels of student participation and understanding. To address these challenges, teachers need to implement appropriate learning strategies to ensure that the process is more directed, effective, and aligned with the allocated time. One effective strategy is appointing proactive students to initiate discussions. These findings indicate that teachers’ ability to manage time is a crucial factor in the successful implementation of CTL-based learning.